Case report: BTK inhibitors is effective in type II mixed cryoglobulinemia with wild-type MyD88 - Xu, Mingyue; Xu, Yunyu; Yuan, Li; Shang, Da; Chen, Ruiying; Liu, Shaojun; Li, Yan; Liu, Aiping; Liu, Ruilai; Wang, Qian; Ding, Tianling; Xie, Qionghong; et al. (Frontiers in Immunology, 2024)
This study presents two cases of type II mixed cryoglobulinemia. One case is essential, while the other is presumably associated with hepatitis B virus (HBV) infection. Both patients tested positive for monoclonal IgMκ, but negative for MyD88 mutation. They showed resistance to rituximab combined with a glucosteroid regimen, but responded positively to BTK inhibitors. These cases highlight the remarkable effectiveness of BTK inhibitors in treating refractory type II cryoglobulinemia without MyD88 mutation. The first patient achieved rapid complete remission of nephrotic syndrome within one month of starting ibrutinib, along with a significant reduction in cryoglobulin levels and abnormal clonal cells. The second patient had a rapid disappearance of rash within three days and accelerated wound healing within one week of initiating orelabrutinib, accompanied by a reduction in C-reactive protein. However, there was no reduction in cryoglobulin levels during the 12-month follow-up. These findings suggest varied mechanisms of action of BTK inhibitors in type II cryoglobulinemia through different mechanisms.